Hubungan Jumlah Leukosit dan Trombosit terhadap Lama Rawat Inap Pasien Demam Berdarah Dengue Anak di RSUD Drs. H. Amri Tambunan Deli Serdang - Marpaung, Okto; Jayanti, Irma; Saragih, Rini A C (Universitas HKBP Nommensen, 2024)
ABSTRACT Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus, characterized by leukopenia and thrombocytopenia. In patients with DHF, when the platelets are <100,000, the Hb and Ht increase and the platelets normal or decrease; the patient must be hospitalized. Objective: To determine the relationship between the number of leukocytes and platelets on the duration of stay of pediatric DHF patients. Methods: This study used an observational analytic research design with a cross-sectional design in September 2022. Data collection was only done once and used secondary data from patients' medical records at Drs. H. Amri Tambunan Deli Serdang. A total of 56 medical records were obtained using the purposive sampling technique. Results: Based on gender, 32 people (57.1%) were male, the majority aged 11-17 years were 31 people (55.4%), and in BMI malnutrition, there were 28 people (50.0%)). Based on the leukocyte count of ≤ 5,000 cells/µL in 37 people (66.1%), while the platelet count was <100,000 cells/µL in 32 people (57.1%), and length of stay > 4 days totaled 39 people (69.6%). Spearman's correlation test results were obtained (p=0.318) for the variable leukocyte count and got (p=0.047) for the variable platelet count. The number of leukocytes did not significantly correlate with the length of stay of DHF children. In contrast, the number of platelets correlate considerably with the duration of stay of children with DHF. Conclusion: There is no significant correlation between the number of leukocytes and the length of stay of pediatric DHF patients, while there is a significant correlation between the number of platelets and the duration of stay of pediatric DHF patients. Keywords: DHF in Children, Leukocytes, Platelets, Length of Hospitalization